2006
DOI: 10.1371/journal.pgen.0020031
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Capsular Biosynthetic Locus from All 90 Pneumococcal Serotypes

Abstract: Several major invasive bacterial pathogens are encapsulated. Expression of a polysaccharide capsule is essential for survival in the blood, and thus for virulence, but also is a target for host antibodies and the basis for effective vaccines. Encapsulated species typically exhibit antigenic variation and express one of a number of immunochemically distinct capsular polysaccharides that define serotypes. We provide the sequences of the capsular biosynthetic genes of all 90 serotypes of Streptococcus pneumoniae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
841
2
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 674 publications
(876 citation statements)
references
References 46 publications
25
841
2
8
Order By: Relevance
“…The chemical structures suggest that WcjE acetylates the 5-and 6-positions of 3-␤-Galf in the polysaccharides of both serotypes. This is consistent with other reports of O-acetylation in serotypes 20, 31, 33A, 35A, and 47A (2), which also carry wcjE (11,16). Thus, WciG acetylates the 2-position of the 6-␤-Galf in the serotype 35C repeat unit, and 2-OAc␤Galf ("OAc" represents O-acetylation) is essential for factor serum 35a recognition.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The chemical structures suggest that WcjE acetylates the 5-and 6-positions of 3-␤-Galf in the polysaccharides of both serotypes. This is consistent with other reports of O-acetylation in serotypes 20, 31, 33A, 35A, and 47A (2), which also carry wcjE (11,16). Thus, WciG acetylates the 2-position of the 6-␤-Galf in the serotype 35C repeat unit, and 2-OAc␤Galf ("OAc" represents O-acetylation) is essential for factor serum 35a recognition.…”
Section: Discussionsupporting
confidence: 92%
“…They are the targets of many serotyping reagents, innate immune molecules (e.g., ficolin-2 [14,18] and siglecs [19]), and vaccine-elicited antibodies (20). Pneumococcal cps loci harbor many acetyltransferase genes (11), and several serogroups contain serotype pairs: one with a functional transferase and the other with nonfunctional transferase. For example, WcjE-positive and -negative pairs have been observed in serogroups 9, 11, and 33 (11,21).…”
Section: -H 1-c 2-h 2-c 3-h 3-c 4-h 4-c 5-h 5-c 6-h 6-c 35c (Smentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that extracellular PSs of Streptococcus thermophilus (39) and group B Streptococcus capsular PSs are highly diverse (6). It is well-known that pathogenic bacteria, such as hemolytic streptococci, often change their outer surface glycan profile to escape the host immune defense mechanism (5). To investigate the dynamism and diversity of bacterial outer surface structures, especially bacterial glycomes, in relation to their functional characterization, a powerful methodology with high throughput and versatility is needed.…”
mentioning
confidence: 99%
“…The biosynthesis of many lipopolysaccharide (LPS) O-antigens (Oags), enterobacterial common antigen (ECA) and some capsule polysaccharides (CPSs) in Gram-negative and Gram-positive bacteria occurs by a mechanism known as the Wzy polymerasedependent pathway [1][2][3][4]. The process relies on a putative, multifunctional protein complex involving homologues of the inner membrane proteins Wzx, Wzy and Wzz [5].…”
Section: Wzy-dependent Polysaccharide Biosynthesismentioning
confidence: 99%